Application of trait and factor theory for career planning in Class XII transitional students at Islamic Senior High School, Karimun - Anggi, Anggi Dwi Noperlis; Afdal, Afdal; Hariko, Rezki; Suhertina (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2023)
Career is an important thing in human life. This is because there is an urge to improve in life. One alternative solution to help someone who has difficulty making career decisions is through the application of trait and factor theory. Trait and factor theory is a career counseling theory that views the right career choice when there is a match between the client's nature and job or position factors. This research is a descriptive qualitative research. The research was conducted at MAN Karimun. The research informants were 1 counseling teacher and 3 transitional class XII students. This study aims to examine in depth the application of trait and factor theory in the career planning of class XII students in the transition period at MAN Karimun. The results of the study show that the application of trait and factor career counseling theory can be an alternative solution to assist clients in planning and making career decisions.